THE ROLE OF WORK STRESS IN MEDIATING THE EFFECT OF WORKLOAD AND WORK ENVIRONMENT ON TURNOVER INTENTION: A STUDY OF ANDY MUSHROOM BOGOR EMPLOYEES - Fadia Fadhilatunnisa; Sri Harini; Ismartaya Ismartaya (Universitas Nusa Cendana, 2026)
This study aims to examine the moderating role of job stress in the relationship between workload, working conditions, and employees’ turnover intentions at Andy Mushroom Bogor. A saturated sampling technique was employed to determine the sample. The findings indicate that workload and job stress have a positive effect on turnover intentions, while working conditions exert a negative influence on employees’ intention to leave. In addition, workload is positively associated with job stress, whereas favorable working conditions are found to reduce job stress. Job stress mediates the positive relationship between workload and turnover intentions and moderates the negative effect of working conditions on turnover intentions. Keywords: Workload; Work Environment; Work Stress: Turnover Intention